Applying hybrid effectiveness-implementation studies in equity-centered policy implementation science - Asada, Yuka; Kroll-Desrosiers, Aimee; Chriqui, Jamie F.; Curran, Geoffrey M.; Emmons, Karen M.; Haire-Joshu, Debra; Brownson, Ross C. (Frontiers in Health Services, 2023)
Policy implementation science (IS) is complex, dynamic, and fraught with unique study challenges that set it apart from biomedical or clinical research. One important consideration is the ways in which policy interacts with local contexts, such as power and social disadvantage (e.g., based on ability, race, class, sexual identity, geography). The complex nature of policy IS and the need for more intentional integration of equity principles into study approaches calls for creative adaptations to existing implementation science knowledge and guidance. Effectiveness-implementation hybrid studies were developed to enhance translation of clinical research by addressing research questions around the effectiveness of an intervention and its implementation in the same study. The original work on hybrid designs mainly focused on clinical experimental trials; however, over the last decade, researchers have applied it to a wide range of initiatives and contexts, including more widespread application in community-based studies. This perspectives article demonstrates how effectiveness-implementation hybrid studies can be adapted for and applied to equity-centered policy IS research. We draw upon principles of targeted universalism and Equity in Implementation Research frameworks to guide adaptations to hybrid study typologies, and suggest research and engagement activities to enhance equity considerations; for example, in the design and testing of implementing strategies. We also provide examples of equity-centered policy IS studies. As the field of policy IS rapidly evolves, these adapted hybrid type studies are offered to researchers as a starting guide.